ANALISIS HASIL BELAJAR FISIKA MELALUI PEMBELAJARAN MENGGUNAKAN HYPERMEDIA PADA PESERTA DIDIK SMAN 9 MAKASSAR - Wahyu Nugraha; Usman Usman; Pariabti Palloan (Lembaga Penelitian Mahasiswa Penalaran UNM, 2023)
This study entitled Analysis of Physics Learning Outcomes through Learning Using Hypermedia for Students of SMAN 9 Makassar is a survey research conducted to measure physics learning outcomes and learning completeness of class XI MIA students at SMAN 9 Makassar through learning using hypermedia in the 2021/2022 school year. The variable in this study is the results of students' physics learning. The research subjects were students of class XI MIA III, XI MIA V and XI MIA VI at SMAN 9 Makassar, totaling 76 people who had attended learning using hypermedia. The research data obtained by giving tests in the form of learning outcomes instruments. The data analysis technique used is descriptive statistical analysis technique. Based on the results of the research and discussion, it can be concluded that the learning outcomes of physics through learning using hypermedia are in the sufficient category with an average score of 9 with a classical learning completeness percentage of 6.58%, this is because in the learning process there is a reduction in study time due to the impact of the covid 19 outbreak, the lack of student activity in participating in learning using hypermedia and the lack of availability of tools that can access hypermedia.